Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Pada PT Asia Paramita Indah Batam - Realize Realize; Sudjono Sudjono (LPPM Universitas Putera Batam, 2023)
Increasing economic growth, is expected to be directed to increase public incomes and fulfill daily needs. The purpose of this study is to determine the effect of Variable service quality (X1) price (X2), and promotion (X3) on purchasing decisions In PT Asia Paramita Indah Batam (Y). In this study, the sampling process is done by using non probability sampling which is a sampling technique that does not provide equal opportunities to be selected into the sample, for this sampling of this author using saturated sampling method. Based on the above sampling technique using saturated sampling technique from the total population of 135 people, then taken as sample is 135 people. Data were collected using questionnaires measured by Likert scale. This study uses multiple linear regression analysis with the help of SPSS version 20.0 program. The results of this study indicate that the variable quality of service (X1) price (X2), and promotion (X3) simultaneously affect the purchase decision In PT Asia Paramita Indah Batam. Variable quality of service (X1) price (X2), and promotion (X3) partially influence partially on purchasing decision In PT Asia Paramita Indah Batam.